Governing digitally integrated genetic resources, data, and literature : global intellectual property strategies for a redesigned microbial research commons - Reichman, J. H. (Cambridge, 2016)
"The free exchange of microbial genetic information is an established public good, facilitating research on medicines, agriculture, and climate change. However, over the past quarter-century, access to genetic resources has been hindered by intellectual property claims from developed countries under the World Trade Organization's TRIPS Agreement (1994) and by claims of sovereign rights from developing countries under the Convention on Biological Diversity (CBD) (1992). In this volume, the authors examine the scientific community's responses to these obstacles and advise policymakers on how to harness provisions of the Nagoya Protocol (2010) that allow multilateral measures to support research. By pooling microbial materials, data, and literature in a carefully designed transnational e-infrastructure, the scientific community can facilitate access to essential research assets while simultaneously reinforcing the open access movement. The original empirical surveys of responses to the CBD included here provide a valuable addition to the literature on governing scientific knowledge commons"--